Medicare Reform: Obstacles and Options - Antos, Joseph R; Bilheimer, Linda (American Economic Review, 1999)
Medicare is the second-largest federal entitlement program after Social Security, and the single largest health insurer in the United States. In 1999, the Medicare program will spend $230 billion, about 13 percent of the federal budget, on behalf of some 39 million elderly and disabled individuals. For the past three decades, Medicare spending has grown substantially faster than the economy and faster than private health spending. That growth has been a continuing concern to policymakers. Financial pressures on the Medicare program will grow dramatically in the next few decades due to changing demographics and to the growth of medical technology. Aging baby-boomers will place unprecedented demands on the program as they reach age 65, beginning in 2011. Enrollment is projected to be 47 million people by 2010, growing to about 75 million people by 2030. Medicare will have more beneficiaries, and more at older ages as longevity increases, than ever before. And the cost per beneficiary of providing health care, which has risen dramatically in the past, is likely to be significantly higher than it is today. Assuming no change in policy, Medicare spending will grow from 2.6 percent of GDP in 1995 to 6.3 percent of GDP in 2030, as the last of the boomers enroll in the program. Meanwhile, the ratio of active workers to retirees will fall, making the current system of financing difficult to maintain without tax increases or substantial cost reductions.